Validation of an Instrument to Measure the Level of Safety Culture in Peru - Gutiérrez-Falcón, Pablo (2025)
Objective: Workplace safety culture plays a critical role in preventing occupational risks and improving worker well-being. However, despite existing regulations, its implementation remains inconsistent in various industries. This study aims to validate an instrument for measuring the level of safety culture in Peru to identify critical improvement areas and support evidence-based strategies. Method: A three-part validation was conducted: selection of the instrument through a review of the scientific literature, qualitative validation through expert judgment, and quantitative validation via a pilot test with 42 workers. Reliability was assessed using Cronbach’s alpha and McDonald’s omega, while construct validity was examined using Exploratory Factor Analysis with Unweighted Least Squares and Promax rotation. Results: The validated instrument consists of 16 questions grouped into five dimensions: a) active participation in safety, b) awareness and compliance with safety regulations, c) risk knowledge and safety training, d) concern for safety and adherence to procedures, and e) prevention and communication about safety. The final model demonstrated good internal consistency (Cronbach’s α = 0.822, Omega = 0.83) and a stable factorial structure, explaining 75.79% of the variance. Conclusions: This validated questionnaire is a reliable tool for assessing safety culture in companies in Peru, allowing organizations to identify weaknesses and implement targeted safety interventions.